PERFORMANCE OF PADDY~ CUM- PRAWN CULTURE IN RAINFED LOW LAND ECOSYSTEM OF SUNDERBANS - MAITI, D.; CHAKRABORTY, P. B. (Journal of Indian Fisheries Association, 2015)
Performance of both paddy (Var. NC 492) and prawn Penaeusmonodon) were assessed for two years during wet-season in rainfedlowland ecosystem with a view to study the economic viability of paddycum-prawn culture in the coastal saline zone of West Bengal. Bothmono and dual culture of paddy and prawn were tried in the study.Fingerlings of prawn(@ 35,000 ha-1) of 10-15 mm size were reared forabout three and half months with and without fish feed. It was observedthat addition offish feed resulted in higher (57.7%) production of prawn(2.65 mgha-1) but not rice. Such increase in prawn productiQn was 1.6times higher when no feed was provided and 1.4 times higher whengrown as sole crop. However, paddy, whether grown as mono or mixedculture, did not differ in yield significantly. In dual culture, the benefitm cost ratio was higher (6.83) when prawn was grown with feed and itwas maximum (36.0) when grown without feed as sole crop. The study,therefore, indicates that paddy-cum-prawn culture under low landecosystemÂ· of the coastal saline zone is enterprising particularly forsmall and marginal farmers who fear to take risk of growing prawnalone at the cost of paddy.